DENTITY CRISIS IN ANDREA LEVY’S SMALL ISLAND (2004) A part of an MA Thesis entitled as (Identity Crisis in Multicultural London: A Study of Andrea Levy’s Small Island and Monica Ali’s Brick Lane) - Juan Abdulla Ibrahim; Shara Jamal Shahoyi (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
The most central topic of discussion in social and cultural research field today is that of identity. Identity is a socio cultural phenomenon which is closely related to the sense of belonging. When immigrants move from one place to another, such sense no longer accompanies them, when this takes place, they often undergo an identity crisis. Andrea Levy presents the immigrant experience in her novel Small Island by focusing on two immigrants who settle in London. Then, the characters, Gilbert and Hortense go through an identity crisis. These characters do not feel welcomed because of racism and prejudice. They feel alienated instead. This study focuses on the immigrant’s experiences and the loss of belonging which ultimately activates an identity crisis. It will also highlight Levy’s formulation of identity which will lead to the creation of strong hybrid identities.